2007
DOI: 10.1080/08860220601098870
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerobic Exercise on Microalbuminuria and Enzymuria in Type 2 Diabetic Patients

Abstract: Increased urinary albumin excretion is a strong predictor for the development of overt diabetic nephropathy and overall cardiovascular morbidity and mortality in patients with type 2 diabetes. In a previous study, regular aerobic physical activity in overweight/obese patients with type 2 diabetes mellitus was found to have significant beneficial effects on glycemic control, insulin resistance, cardiovascular risk factors, and oxidative stress. The aim of the present study was to investigate the effects of aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 18 publications
1
34
0
2
Order By: Relevance
“…We found no evidence that PA participation worsens resting proteinuria in persons with type 1 or type 2 diabetes (Garg et al 1995;Groop et al 1990). Despite hypothetical adverse effects of increased proteinuria immediately after exercise, existing data show no progression of nephropathy with exercise and, in fact, increasing PA may decrease existing albuminuria (a type of proteinuria) (Fredrickson et al 2004;Lazarevic et al 2007). In cross-sectional studies, increased PA is associated with a decreased risk of developing nephropathy (Kriska et al 1991;Wadén et al 2008).…”
Section: Kidney Diseasementioning
confidence: 54%
“…We found no evidence that PA participation worsens resting proteinuria in persons with type 1 or type 2 diabetes (Garg et al 1995;Groop et al 1990). Despite hypothetical adverse effects of increased proteinuria immediately after exercise, existing data show no progression of nephropathy with exercise and, in fact, increasing PA may decrease existing albuminuria (a type of proteinuria) (Fredrickson et al 2004;Lazarevic et al 2007). In cross-sectional studies, increased PA is associated with a decreased risk of developing nephropathy (Kriska et al 1991;Wadén et al 2008).…”
Section: Kidney Diseasementioning
confidence: 54%
“…20,21,40 Moderate exercise also prevented reduction in GFR and attenuated albuminuria in spontaneously hypertensive rats 23 and in diabetic and cardiopathic human. 24,25 Although the mechanisms by which moderate exercise training improves renal function are not fully understood, there are evidences indicating that the better metabolic control, reduction of oxidative stress, and increased production and bioavailability of NO may be involved in this process. 20,21,23,40 In fact, aerobic training during eight weeks induced better metabolic control, reduction of thiobarbituric acid reactive substance (TBARS), and increased NO production, delaying the progression of diabetic nephropathy in STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that exercise training of moderate intensity, besides benefiting metabolic control, improves the kidney function, reduces microalbuminuria, restores oxidative balance and increases nitric oxide (NO) bioavailability in STZ-induced diabetic rats, [20][21][22] spontaneously hypertensive rats 23 and humans. 24,25 However, the mechanisms underlying the benefits of exercise on the diabetic kidney are poorly understood, and the evidences for the renal effects of previous exercise training in diabetic females are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Carnosines are secreted into the circulation by skeletal muscle cells during physical exercise, which is in line with the beneficial effects of physical exercise on diabetic complications [17,18]. Our recent study shows that the kidney has its own carnosine metabolism [19].…”
Section: Introductionmentioning
confidence: 62%